2021
DOI: 10.1093/toxsci/kfab066
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Exposure to Domoic Acid Disrupts Startle Response Behavior and Circuitry in Zebrafish

Abstract: Harmful algal blooms produce potent neurotoxins that accumulate in seafood and are hazardous to human health. Developmental exposure to the harmful algal bloom toxin, domoic acid (DomA), has behavioral consequences well into adulthood, but the cellular and molecular mechanisms of DomA developmental neurotoxicity are largely unknown. To assess these, we exposed zebrafish embryos to DomA during the previously identified window of susceptibility and used the well-known startle response circuit as a tool to identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…Previous studies showed that exposure at 2 dpf (0.14 ng, injected at 48-52 hpf) led to startle response deficits and myelin defects, whereas exposures at 1 dpf (injected at 28-32 hpf) did not lead to any of these effects. 27,28 We sought to determine whether, as seen for the behavioral and myelin phenotypes, the loss of Mauthner cells does not occur after exposure at 1 dpf. Even though the Mauthner cells were present at the time of exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that exposure at 2 dpf (0.14 ng, injected at 48-52 hpf) led to startle response deficits and myelin defects, whereas exposures at 1 dpf (injected at 28-32 hpf) did not lead to any of these effects. 27,28 We sought to determine whether, as seen for the behavioral and myelin phenotypes, the loss of Mauthner cells does not occur after exposure at 1 dpf. Even though the Mauthner cells were present at the time of exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DomA-induced disruptions to myelin sheath formation in the central nervous system 27,28 led us to look into the effects of DomA on cells of the oligodendrocyte lineage, which are responsible for myelinating the central nervous system. 29,30 Successful myelination requires oligodendrocyte precursor cells (OPCs) to form, migrate, differentiate into oligodendrocytes, and then initiate the process of myelination in different regions within the nervous system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vibroacoustic startle latency was assessed as described previously 37 , 38 and the same set-up was used to test for startle habituation as a form of non-associative learning in 6 dpf larval zebrafish. For each trial, 16 larvae with inflated swim bladders were distributed in a 4 × 4 acrylic well-plate which was mounted on a minishaker (Brüel & Kjaer, Vibration Exciter 4810) connected to an amplifier (Brüel & Kjaer, Power Amplifier Type 2718).…”
Section: Methodsmentioning
confidence: 99%